FEATURES OF SURGICAL TACTICS OF TREATMENT OF ACUTE CALCULOUS CHOLECYSTITIS OCCURRING AGAINST THE BACKGROUND OF DIABETES MELLITUS - V. V. Zorik; G. K. Karipidi; A. V. Morozov (Кубанский научный медицинский вестник, 2018)
Aim. The study was conducted to improve the results of the surgical treatment of acute calculous cholecystitis occurring against the background of diabetes mellitus. Materials and methods. In course of our study, we analyzed the treatment results of 687 patients with acute calculous cholecystitis. Depending on the presence of diabetes, all patients were divided into two groups. The main group with concomitant diabetes mellitus included 68 (9,9%) patients, whereas the control group without diabetes included 619 (90,1%) patients. Laparoscopic cholecystectomy was performed on 636 (92,6%) patients, and open cholecystectomy was performed on 51 (7,4%) patients. Results. According to the histological study, the greatest number of destructive forms occurs in patients with concomitant diabetes, operated after 24 hours. The least postoperative complications occur in patients of both groups operated from 12 to 24 hours. However, the incidence of complications is 4-5 times higher in patients with diabetes mellitus. Postoperative complications in patients with acute calculous cholecystitis occurring on the background of sugar diabetes were observed after open cholecystectomy in 33,3% of cases and in 6,5% of cases after laparoscopic surgery.Conclusion In patients with acute cholecystitis and concomitant diabetes, surgical treatment should be performed on the first day after the preoperative preparation during the first 12 hours, aimed at compensating for diabetes and improving microcirculation. The preference should be given to laparoscopic cholecystectomy, which reduces the number of postoperative complications by 5 times and mortality by 4.5 times.